Resolving the developmental distribution patterns of polyphenols and related primary metabolites in bilberry (Vaccinium myrtillus) fruit. (16th April 2022) - Dare, Andrew P.; Günther, Catrin S.; Grey, Angus C.; Guo, George; Demarais, Nicholas J.; Cordiner, Sarah; McGhie, Tony K.; Boldingh, Helen; Hunt, Martin; Deng, Cecilia; Karppinen, Katja; Jaakola, Laura; et al.
Highlights: Mass spectrometry imaging reveals the spatial localisation of bilberry fruit metabolites. Anthocyanins and flavonols accumulate in a fruit skin-to-flesh gradient. Soluble carbohydrates correlate with anthocyanin biosynthesis in contrast to amino acids. Spatial segmentation analysis suggests that ripening proceeds from the skin into the flesh. Abstract: Bilberry ( Vaccinium myrtillus ) is a commercially important wild berry species, which accumulates high amounts of polyphenols, particularly anthocyanins, in the skin and flesh. Whilst a number of studies have quantified these phytochemicals in intact ripe bilberry fruit, we extend the current knowledge by investigating the spatial distribution of anthocyanin-associated polyphenols in fruit tissue, and study their links with primary metabolism during ripening. To address this, we used LC-MS and mass spectrometry imaging to measure and map primary and secondary metabolites in fruit. Correlation analysis showed that five sugars displayed strong positive correlations with anthocyanin accumulation, whereas all amino acids were negatively correlated. The accumulation patterns of polyphenols correlated in fruit skin and flesh, but altered with development. Finally, spatial segmentation analysis revealed that the chemical signatures of ripening first appear at defined regions under the skin and rapidly expand to encompass the entire fruit at the eating-ripe stage.